High-Sensitivity C-Reactive Protein is Related to Central Obesity and the Number of Metabolic Syndrome Components in Jamaican Young Adults - Bennett, Nadia R.; Ferguson, Trevor S.; Bennett, Franklyn I.; Tulloch-Reid, Marshall K.; Younger-Coleman, Novie O. M.; Jackson, Maria D.; Samms-Vaughan, Maureen E.; Wilks, Rainford J. (Frontiers in Cardiovascular Medicine, 2014)
Background High-sensitivity C-reactive protein (hsCRP) has been shown to predict cardiovascular disease (CVD) endpoints and is associated with CVD risk factors and the metabolic syndrome. This study evaluated the association between hsCRP and CVD risk factors among Afro-Caribbean young adults in Jamaica. Methods We conducted a cross-sectional analysis of data from the Jamaica 1986 Birth Cohort Study. Data were collected between 2005 and 2007 when participants were 18-20 years old. All participants completed an interviewer administered questionnaire and had anthropometric and blood pressure (BP) measurements performed. Fasting blood samples were collected for measurement of glucose, lipids and hsCRP. Logistic regression models were used to identify factors independently associated with high hsCRP. Results Analyses included 342 men and 404 women with mean age 18.8 ± 0.6 years. Approximately 15% of the participants had high risk hsCRP (>3 mg/L), with a higher prevalence among women (20% vs. 9%; p<0.001). The prevalence of elevated hsCRP increased with BMI category, high waist circumference (WC), high triglycerides, low HDL, and lower parental education among women, but only for high WC and lower parental education among men. In logistic regression models controlling for sex and parental education, high WC was associated with significantly higher odds of high hsCRP (OR 7.8, 95%CI 4.8-12.9, p<0.001). In a similar model high hsCRP was also associated with the number of metabolic syndrome components. Compared to participants with no metabolic syndrome component, having one metabolic syndrome component was associated with a two-fold higher odds of high hsCRP (OR 2.2, 95%CI 1.3-3.8, p=0.005), while having three components was associated with a fourteen-fold higher odds of high hsCRP (OR 13.5, 95%CI 2.4-76.0, p<0.001). Conclusion High hsCRP is common among Jamaican young adults and is strongly associated with central obesity and the number of metabolic syndrome components.